Penerapan Model Pembelajaran Inkuiri Learning Terhadap Kemampuan Berpikir Tinggi Siswa Kelas X Di MAN 3 Pekanbaru - Saryati, Ayu; Sukenti, Desi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The Inquiry Learning model can improve students' higher-order thinking skills. This indicates that, theoretically, Inquiry Learning has an influence on higher-order thinking skills. The Inquiry Learning model in this study aims to provide a better impact on students' higher-order thinking in the material of writing observation report texts. This research employs a quasi-experimental method. The research design used in this type of study is the non-equivalent control group design. The researcher selected class X Science 1 as the experimental class, consisting of 34 students, using the Inquiry Learning model, and class X Science 2 as the control class, consisting of 35 students, which followed the regular teaching model. The learning outcome test used in this research is a test of student learning outcomes during the learning process. The tests used consist of pretests and post-tests. The research results found an improvement in students' understanding of the material before and after the Inquiry Learning model was applied. In the experimental class, there was an increase in students' ability to understand the material of writing observation texts delivered by the teacher. The hypothesis test results show that the significance value is 0.000. Since the significance value of 0.000 < 0.05, it can be concluded that the application of the Inquiry Learning model is capable of improving students' higher-order thinking skills.